The Image of Financial Institution as Islamic Bank In Mediation Service Quality and Customer Satisfaction on Customer Loyalty in Purwokerto. - Warsito, Chandra (UNIVERSITAS ISLAM NEGERI SYARIF HIDAYATULLAH JAKARTA, 2015)
The paper aims to determine the effect of service quality on customer satisfaction, service quality, customer satisfaction and image on customer loyalty, quality of service to the company’s image, to determine the image of financial institutions in mediating the relationship variable quality of service and customer satisfaction on customer loyalty. The samples used were 110 customers and methods of analysis used is Structural Equation Modeling (SEM) test results find no significant effect of service quality on customer satisfaction; quality of service loyalty; customer satisfaction on customer loyalty; quality of service to the image of the company; customer satisfaction with the company’s image; and the image of the company loyalty; Image of financial institutions PT. BPRS BAS can be used as a variable relationship mediation variable service quality and customer satisfaction on customer loyalty.DOI: 10.15408/aiq.v7i2.1699